42.5k views
3 votes
Factor the polynomial: -x^3-2x^2-3x

User Lanery
by
4.9k points

2 Answers

1 vote

Answer:

Explanation:

-x is common to all three terms. Thus, -x^3-2x^2-3x = -x(x^2 + 2x + 3).

Use the quadratic formula to find the roots (and thus the factors) of

x^2 + 2x + 3: a = 1; b = 2; c = 3.

Thus, the discriminant is b^2-4ac, or 4 - 4(1)(3), or -8.

Because this discriminant is negative, x^2 + 2x + 3 has two complex, unequal roots. They are:

-2 ± i√8

x = -------------- or -1 ± i*2*√2

Thus, the three factors of the given polynomial are:

-x, (x + 1 + 2i√2), and (x + 1 - 2i√2)

2

User Deltics
by
5.1k points
2 votes

Answer:

-x(x^2+2x+3)

Explanation:

User Stephen Watkins
by
4.9k points